STUDI KANDUNGAN LOGAM Pb DALAM TANAMAN KANGKUNG UMUR 3 DAN 6 MINGGU YANG DITANAM DI MEDIA YANG MENGANDUNG Pb - Kohar, Indrajati; poppy_hardjo@ubaya.ac.id, Poppy Hartatie; Lika, Imelda Inge (Makara Journal of Science, 2005)
Study on Pb Content in 3 Week and 6 Week Old Kangkung (Ipomoea reptans Poir) Planted in Pb containing Media. A study on the content of Pb in kangkung has been conducted. Land kangkung (Ipomoea reptans) was used as the sample, and was planted in hydrophonic media, and watered with Multigrow Complete Plant Food (2000 mg/L) and Pb solution (2 mg/L) twice a day. Samples were taken based on the age (3 and 6 week old), and part of the plant (root and all parts without root). Inductively Coupled Plasma Spectrometer (ICPS) Fison 3410+ was used to measure the Pb content. It was shown that in the plant the accumulation was mostly happened in the root. The 6 week-old plant contained Pb not just in the root (3.36 mg/kg sample) but also in the other part of the plant (2.09 mg/kg sample) and those were exceeded the maximum dietary allowance (2 mg/kg sample) regulated by the Indonesian FDA; while in the 3 week-old plant the Pb content in the root was 1.86 mg/kg sample and in the other part of the plan was 1.13 mg/kg, which is not exceeded the dietary allowance. So it is advisable to harvest the kangkung vegetable at the most of 3 week-old.